Study on extraction and antibacterial activity of aucubin from Eucommia ulmoides seed-draff waste biomass - Yunhui Liao; Feng Chen; Lujie Xu; Wubliker Dessie; Jiaxing Li; Zuodong Qin (Heliyon, 2022)
Aucubin (AU) is an active ingredient exerting strong antioxidant and anti-inflammatory effects in treating several diseases. This study evaluated the extraction of AU from Eucommia ulmoides seed-draff (EUSD) waste biomass using a series of solvents (methanol, ethanol, i-propanol, n-propanol, n-butanol, n-pentanol and cyclohexane) assisted with microwave and ultrasound, and proposed the optimized method for extraction. Five factors were investigated by Box-Behnken design (BBD) and response surface methodology (RSM). The optimized extraction conditions were as follows: liquid-solid ratio of 46.37 mL/g, methanol percentage of 89.56%, ultrasonic (extraction) time of 59.95 min, microwave power of 306.73 W, and microwave (extraction) time of 18.93 s. To this end, the AU extraction reached the maximum value (149.1 mg/g), which was consistent with the theoretical value (149.3 mg/g). Furthermore, the kinetics of extraction process were investigated by mathematic modeling. The extraction process analysis was also explored by 1H nuclear magnetic resonance (1H-NMR) spectroscopy, Fourier transform infrared (FTIR) spectroscopy and COSMOtherm program. This study found out that methanol provided better extraction efficiency than the conventional solvents (water, ethanol, i-propanol, n-propanol, n-butanol, n-pentanol, cyclohexane) due to possible interactions by the formation of hydrogen bond between AU and methanol, and ultrasound and microwave could significantly enhance mass transfer, which exhibited higher extraction efficiency and lower energy consumptions (149.1 mg/g and 0.102 kW·h vs. 73.4 mg/g and 0.700 kW·h for Soxhlet extraction). In the antibacterial activity study, the AU extract exerted strong antibacterial ability against 4 tested pathogens, and the antibacterial effect followed the order of: Staphylococcus aureus (35.9 ± 1.32 mm) > Escherichia coli (30.7 ± 1.38 mm) > Bacillus subtilis (20.5 ± 1.36 mm) > Salmonella (15.9 ± 1.39 mm) with the AU concentration of 40 mg/mL. Therefore, the development of this study will help to deepen the further understanding of natural product extraction by methanol-based ultrasonic and microwave, and has certain application value for the development and utilization of natural iridoid glycosides product.